Pengembangan Program Edukasi Keluarga Berbasis Koleksi di Museum Biologi - Pramesti, Narezwari Nindya (JANUS, 2025)
Museum Biologi Universitas Gadjah Mada (UGM) is a university museum with a natural history theme that displays collections of preserved flora and fauna from various regions in Indonesia. The museum serves as educational and research for diverse audiences, including academics, students, teachers, and families. However, no family education program is available despite families being primary learning environments. This article aims to develop an educational program based on museum collections that actively involve families, creates learning, bonds, and shared memories, and increases understanding of museum collections. Through a qualitative approach through observations and interviews, this research explores the needs and expectations of visitor families. The resulting educational program is designed to provide an interactive, fun learning experience and strengthen environmental awareness. === Museum Biologi Universitas Gadjah Mada (UGM) merupakan museum universitas bertema sejarah alam yang memamerkan koleksi awetan flora dan fauna dari berbagai daerah di Indonesia. Museum Biologi berperan sebagai sarana edukasi dan penelitian bagi berbagai kalangan seperti akademisi, siswa dan guru, serta keluarga. Namun, belum tersedia program edukasi khusus keluarga, meskipun keluarga merupakan lingkungan belajar utama. Artikel ini bertujuan mengembangkan program edukasi berbasis koleksi museum yang melibatkan keluarga secara aktif, menciptakan pembelajaran, ikatan dan memori bersama, serta meningkatkan pemahaman terhadap koleksi museum. Melalui pendekatan kualitatif melalui observasi dan wawancara, penelitian ini mengeksplorasi kebutuhan dan harapan keluarga pengunjung. Program edukasi yang dihasilkan dirancang untuk memberikan pengalaman belajar yang interaktif, menyenangkan, dan memperkuat kesadaran lingkungan.